Effects of propofol and sevoflurane on hepatic blood flow: a randomized controlled trial - Jurgen van Limmen; Piet Wyffels; Frederik Berrevoet; Aude Vanlander; Laurent Coeman; Patrick Wouters; Stefan De Hert; Luc De Baerdemaeker (BMC Anesthesiology, 2020)
Abstract Background Maintaining adequate perioperative hepatic blood flow (HBF) supply is essential for preservation of postoperative normal liver function. Propofol and sevoflurane affect arterial and portal HBF. Previous studies have suggested that propofol increases total HBF, primarily by increasing portal HBF, while sevoflurane has only minimal effect on total HBF. Primary objective was to compare the effect of propofol (group P) and sevoflurane (group S) on arterial, portal and total HBF and on the caval and portal vein pressure during major abdominal surgery. The study was performed in patients undergoing pancreaticoduodenectomy because - in contrast to hepatic surgical procedures - this is a standardized surgical procedure without potential anticipated severe hemodynamic disturbances, and it allows direct access to the hepatic blood vessels. Methods Patients were randomized according to the type of anesthetic drug used. For both groups, Bispectral Index (BIS) monitoring was used to monitor depth of anesthesia. All patients received goal-directed hemodynamic therapy (GDHT) guided by the transpulmonary thermodilution technique. Hemodynamic data were measured, recorded and guided by Pulsioflex™. Arterial, portal and total HBF were measured directly, using ultrasound transit time flow measurements (TTFM) and were related to hemodynamic variables. Results Eighteen patients were included. There was no significant difference between groups in arterial, portal and total HBF. As a result of the GDHT, pre-set hemodynamic targets were obtained in both groups, but MAP was significantly lower in group S (p = 0.01). In order to obtain these pre-set hemodynamic targets, group S necessitated a significantly higher need for vasopressor support (p < 0.01). Conclusion Hepatic blood flow was similar under a propofol-based and a sevoflurane-based anesthetic regimen. Related to the application of GDHT, pre-set hemodynamic goals were maintained in both groups, but sevoflurane-anaesthetized patients had a significantly higher need for vasopressor support. Trial registration Study protocol number is AGO/2017/002 – EC/2017/0164. EudraCT number is 2017–000071-90. Clin.trail.gov, NCT03772106 , Registered 4/12/2018, retrospective registered.